Home-based rehabilitation for heart failure with reduced ejection fraction: mixed methods process evaluation of the REACH-HF multicentre randomised controlled trial. Issue 8 (2nd August 2019) - Frost, Julia; Wingham, Jennifer; Britten, Nicky; Greaves, Colin; Abraham, Charles; Warren, Fiona C; Jolly, Kate; Doherty, Patrick Joseph; Miles, Jackie; Singh, Sally J; Paul, Kevin; Taylor, Rod; et al.
Abstract : Objective: To identify and explore change processes explaining the effects of the Rehabilitation Enablement in Chronic Heart Failure (REACH-HF) intervention taking account of reach, amount of intervention received, delivery fidelity and patient and caregiver perspectives. Design: Mixed methods process evaluation parallel to a randomised controlled trial using data from the intervention group (REACH-HF plus usual care). Setting: Four centres in the UK (Birmingham, Cornwall, Gwent and York). Participants: People with heart failure with reduced ejection fraction (HFrEF) and their caregivers. Methods: The REACH-HF intervention consisted of a self-help manual for patients with HFrEF and caregivers facilitated over 12 weeks by trained healthcare professionals. The process evaluation used multimodal mixed methods analysis. Data consisted of audio recorded intervention sessions; demographic data; intervention fidelity scores for intervention group participants (107 patients and 53 caregivers); qualitative interviews at 4 and 12 months with a sample of 19 patients and 17 caregivers. Outcome measures: Quantitative data: intervention fidelity and number, frequency and duration of intervention sessions received. Qualitative data: experiences and perspectives of intervention participants and caregivers. Results: Intervention session attendance with facilitators was high. Fidelity scores were indicative of adequate quality of REACH-HF intervention delivery, although indicating scope for improvement in several areas. Intervention effectiveness was contingent on matching the intervention implementation to the concerns, beliefs and goals of participants. Behaviour change was sustained when shared meaning was established. Respondents' comorbidities, socio-economic circumstances and existing networks of support also affected changes in health-related quality of life. Conclusions: By combining longitudinal mixed methods data, the essential ingredients of complex interventions can be better identified, interrogated and tested. This can maximise the clinical application of research findings and enhance the capacity of multidisciplinary and multisite teams to implement the intervention. Trial registration number: ISRCTN25032672 ; Pre-results.